The Implementation Of Balanced Scorecard In Indonesian Companies Companies: A Systematic Literature Review - Mediaty Mediaty; Asri Usman; Fifi Selvi; Lasri Ningsih; Dinda Reskiana Putri (Cita konsultindo, 2023)
The business world cannot be excluded when discussing increasingly competitive competition. To keep up with the development of the industry, it is necessary to measure the performance that is expected. Through this, the company can build its condition in a better direction and be able to participate in the competitive business world. The purpose of this article is to show the benefits of applying the balanced scorecard method to companies in Indonesia. The method used to achieve this goal is a systematic literature review by analyzing the 15 literature findings discussed in this article. The results showed that all 15 companies used four balanced scorecard perspectives simultaneously to measure financial and non-financial performance. Not only that, some literature also shows that the application of a balanced scorecard as a measurement method can provide a more structured and comprehensive picture of the company's overall performance. The findings of the 15 literatures also vary, which indicates that with a balanced scorecard, the company can find out its weaknesses and strengths so that it can be an evaluation material for the company to make improvements in the future.